Current Challenges of Digital Technologies - Leskova, Andrea; Jurjewicz, Hubert; Lenghart, Patrik; Bacik, Peter (Communications - Scientific letters of the University of Zilina, 2018)
This contribution deals with questions on the relationship between reality and virtual reality. It focuses on the problem of shaping an individual’s identity in a digital, online environment and, in this context, identifies a retrospective impact on the real person’s identity. An effort will also be made to name selected problems related to the topic and to point out some risks that the online environment introduces to the field of self-perception, especially in regard to interpersonal relations. As a result, attention is drawn to changes in the value system that are related to the explored questions.